Hubungan Lama Penggunaan Keluarga Berencana (KB) Suntik 3 Bulan dengan Berat Badan pada Wanita Usia Subur (WUS) di Puskesmas Soromandi Kabupaten Bima - Humaediah Lestari; Fitri Pujisustiawati; Arista Kusuma Wardani (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Introduction: 3-month injectable contraceptives is the type of contraception most often chosen by women. The user of injectable contraceptives in some acceptors can cause side effects, one of which is weight gain. Purpuse: The aim of this study was to identify anemia that occurs in patients with chronic renal failure undergoing hemodialysis. The design of this research is descriptive with a cross-sectional approach. Methods: This research will be carried out in This research was carried out at the Suromandi Community Health Center. The population in this study were patients with chronic renal failure (CKD) undergoing hemodialysis. The samples in this study were 3 injection contraceptive acceptors using simple random sampling technique. The instruments used in this research used family planning register book. Result: The results of the study showed that respondents who used injectable contraceptives for ≤ 2 years mostly had normal weight, 39 people (54.2%), as well as respondents who used injectable contraceptives for > 2 years, most of whom had normal weight, 69 people (49 .6%). Suggestions: for future researchers are that they can carry out further research related to weight gain in contraceptive users.